Health Policy and Multidisciplinary Strategies in Addressing Community Health Challenges - Yohan Trayanus Lasarus Djaha (Edukasi Ilmiah Indonesia, 2025)
Increasing complexity of patient needs requires healthcare professionals to collaborate effectively across disciplines while applying evidence-based practice. However, professional silos and inconsistent use of evidence often limit the quality, safety, and coordination of patient care. Evidence-based collaboration across health professions has therefore emerged as a key strategy to improve patient care outcomes. This study aimed to examine the relationship between evidence-based collaboration across health professions and patient care outcomes. A quantitative cross-sectional study was conducted involving 50 health professionals from multiple disciplines, including physicians, nurses, pharmacists, and allied health professionals. Data were collected using a structured questionnaire measuring evidence-based collaboration (shared decision-making, use of clinical guidelines, and interprofessional communication) and patient care outcomes (care coordination, patient safety, and perceived quality of care). Descriptive statistics and linear regression analysis were applied to assess the association between collaboration and patient care outcomes. The findings indicated that respondents reported moderate to high levels of evidence-based collaboration and patient care quality. Regression analysis demonstrated a significant positive association between evidence-based collaboration and patient care outcomes (? = 0.45; p < 0.001). Higher levels of collaborative, evidence-informed practice were particularly associated with improved care coordination, enhanced patient safety, and higher perceived quality of care. Evidence-based collaboration across health professions is significantly associated with better patient care outcomes. Strengthening interprofessional collaboration supported by consistent use of clinical evidence may enhance patient-centered care, safety, and overall quality of healthcare services. These findings underscore the importance of promoting evidence-based collaborative practices within healthcare organizations